Demographics and the Natural Rate of Interest in Japan - Han, Fei (IMF Working Papers; Working Paper ;, 2019)
Japan's aging and shrinking population could lower the natural rate of interest and, together with low inflation expectations, challenge the Bank of Japan's efforts to reflate the economy. This paper uses a semi-structural model to estimate the impact of demographics on the natural rate in Japan. We find that demographic change has a significantly negative impact on the natural rate by lowering trend potential growth. We also find that the negative impact has been increasing over time amid stronger demographic headwinds. These findings highlight the importance of boosting potential growth to offset the negative demographic impact and lift the natural rate in Japan.